Technology challenges among deaf and hard of hearing elders in China during COVID-19 pandemic emergency isolation: A qualitative study - Xu, Di; Ma, Shiwen; Yan, Chu; Zhao, Ziqing (Frontiers in Public Health, 2023)
Digital technology can be an effective tool to facilitate emergency assistance in a pandemic, but many deaf and hard-of-hearing elders may experience challenges in using and adopting these technologies. In the context of the second wave of the COVID-19 outbreak, this study employs a qualitative research method based on in-depth interviews to explore technology challenges among deaf and hard-of-hearing elders in China. The results showed that this group's technology challenges arose mainly from barriers to the mastery of digital technology tools, among which barriers to the use of smartphones, to the accessibility of online medical consultations, and to the presentation of health codes, were most noteworthy. For the informants, these barriers led to social isolation and technology avoidance. What’s more, the expectation of individuals to adopt certain types of digital intelligence technologies can inadvertently create inequities for disadvantaged groups and exacerbate the "digital divide". This study highlights the need for emergency management systems to be inclusive of elders with hearing loss in times of public health crises, by providing effective technology support and training to facilitate individuals’ access to services and to safeguard their health, interests, and livelihood.